Combinatorial Analysis Methodologies for Accelerated Research: The Case of Chalcogenide Thin‐Film Photovoltaic Technologies. Issue 9 (1st July 2022) - Fonoll-Rubio, Robert; Becerril-Romero, Ignacio; Vidal-Fuentes, Pedro; Grau-Luque, Enric; Atlan, Fabien; Perez-Rodriguez, Alejandro; Izquierdo-Roca, Victor; Guc, Maxim
Abstract : One of the fastest ways for the discovery, understanding, development, and further optimization of new complex materials is the application of combinatorial analysis methodologies, which have already shown impressive results for different organic and inorganic materials, leading to the fast development of different scientific fields and industrial applications. However, in the case of thin‐film materials for optoelectronic devices and, in particular, for second‐generation photovoltaic (PV) devices, the application of combinatorial analysis is still quite uncommon with a desultory rather than systematic application. The present review discusses the main constraints for the application of combinatorial analysis to thin‐film materials with a focus on chalcogenide compounds and different strategies to overcome them. Special attention is paid to the requirements for the preparation of graded thin films, characterization, and analysis of the results, providing different hints for the implementation of high‐quality combinatorial analysis. Finally, an overview of the currently published results in the field of chalcogenide thin‐film PV technologies is presented, showing the relevance of the combinatorial approach for boosting the development not only of this promising PV technology, but also of other optoelectronic devices based on complex materials and multilayered structures. Abstract : This work provides a roadmap for applying combinatorial analysis for the accelerated research of chalcogenide absorber materials and includes a critical review of the requirements for optimal synthesis and characterization techniques, a review of the approaches for suitable processing of the obtained data, and a review of the state‐of‐art combinatorial analysis applied on chalcogenide‐based thin‐film photovoltaic technologies.